The protective mechanism of docosahexaenoic acid in mouse model of Parkinson: The role of heme oxygenase. (December 2016) - Ozkan, Ayse; Parlak, Hande; Tanriover, Gamze; Dilmac, Sayra; Ulker, Seher Nasircilar; Birsen, llknur; Agar, Aysel
Abstract: Parkinson's disease (PD) is characterized by degeneration of the dopaminergic neurons in substantia nigra (SN). Its major clinical symptoms are tremor, rigidity, bradykinesia and postural instability. Docosahexaenoic acid (DHA) is an essential fatty acid for neural functions that resides within the neural membrane. A decline in fatty acid concentration is observed in case of neurodegenerative diseases such as PD. The present study aimed to explore the role of the heme oxygenase (HO) enzyme in protective effects of DHA administration in an experimental model of PD by using the neurotoxin 1-Methly-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). Three-month old male C57BL/6 mice were randomly divided into 4 groups as Control, DHA-treated (DHA), MPTP-injected (MPTP) and DHA-treated + MPTP injected (DHA + MPTP). DHA was administered daily (36 mg kg −1  day −1 ) by gavage to DHA and DHA + MPTP groups for 30 days. On the 23rd day of DHA administration, MPTP was intraperitoneally injected at a dose of 4 × 20  mg kg −1 with 2-hr. intervals. Motor activities of mice were evaluated by pole test, locomotor activity and rotarod tests on the 7th day of the utilization of experimental Parkinson's model. Total brain tissues were used in immunohistochemical analysis of the tyrosine hydroxylase (TH) and Nuclear factor E2 related factor2 (Nrf2). SN tissues were extracted for biochemical analysis. HO-1 and HO-2 protein levels were detected by western blotting. Further, HO activity was measured by spectrophotometric assay. As an indicator of motor coordination and balance, the rotarod test at 40 rpm showed that MPTP-treated animals exhibited shorter time on the rotating rod mill, which was significantly increased by DHA treatment in DHA + MPTP group. The total locomotor activity, ambulatory movement and total distance were decreased in MPTP group, whereas they were improved upon DHA treatment. The results of the pole test indicating the intensity of the bradykinesia showed that the T-turn and T-total were increased in MPTP group, while DHA treatment significantly shortened both parameters. The number of TH-positive cells in SN was significantly reduced in MPTP group compared to the Control and DHA + MPTP groups. Also, immunoreactive Nrf2 levels were clearly increased in MPTP group compared to DHA + MPTP group. HO-1 expression level decreased in the DHA + MPTP group compared to MPTP group. The results of the present study indicated that DHA has protective effects on dopaminergic neurons in MPTP-induced experimental model of PD. In addition, the pathways of HO-1 and HO-2 might participate in this protective mechanism. Highlights: DHA has protective effects on dopaminergic neurons in MPTP-induced experimental Parkinson model. Motor coordination, balance and locomotor activity were decreased in MPTP group whereas, they were significantly improved upon DHA treatment. HO-1 expression was detected to enhance in Parkinson's group compared to control group. Nrf2 expression of cell was significantly increased in MPTP group.